Psicoanálisis e investigación - Altamirano, Patricia; Baldo, Marta; Rigotti, Hebe; Sherman, Patricia (Universidad Nacional de Córdoba, 2016)
Fil: Altamirano, Patricia. Universidad Nacional de Córdoba. Facultad de Psicología; Argentina.